Mental health effects of working as a legal professional in the field of asylum law: a systematic review - Ciarán O'Driscoll; Leah Holt; Jessie Mulcaire; Sana Zard; Francesca Brady (BMJ Publishing Group, 2024)
Aims Legal professionals work closely with asylum seekers at many points during an asylum claim. While there is an increasing literature examining the mental health effects of working with traumatised populations, there has been limited evidence focusing on the field of asylum law. This review aims to synthesise the current qualitative and quantitative literature on the mental health effects of working in asylum law.Method A systematic search from inception to 24 August 2023 was completed on the following databases: Web of Science, PsycINFO, MEDLINE, PubMed, SCOPUS, Westlaw UK, Index to Foreign Legal Periodicals and Index to Legal Periodicals and Books. The search retrieved 11 studies (6 qualitative, 3 quantitative and 2 mixed methods). A thematic synthesis was completed for the qualitative research and a narrative synthesis was completed for the quantitative research, before the findings were integrated into a combined synthesis.Results Four main themes and 13 subthemes were generated by the qualitative research. The main themes were as follows: emotional labour, working in a broken system, emotions do not mix with law and detachment. The quantitative synthesis found a variety of measures used in the literature, indicating that common mental health concerns, such as burn-out, depression, anxiety, post-traumatic stress disorder and secondary trauma symptoms, are present across this professional group. The synthesis also provides preliminary findings relating to possible predictors of poor mental health.Conclusions Despite limited evidence and methodological flaws in the literature, this review indicates that legal professionals are exposed to traumatised clients and difficult working conditions, both of which can negatively impact mental health. It also highlights a number of factors which may predict or perpetuate difficulties. Clinical implications, limitations and suggestions for future research are discussed.